A new magnetic melt spinning device for patterned nanofiber - Kai Zhang (Nature Portfolio, 2021)
Abstract The size and morphology of nanofibers directly determine their application scope and performance, while regular patterned fibers further demonstrate their superior performance in the field of sensors and biomaterials. Melt electrospinning enables controlled deposition of fibers and is currently one of the most important means of preparing patterned fibers. However, due to the existence of high-voltage electric field, melt electrospinning has safety problems such as partial discharge and electric field breakdown, coupled with the charge rejection on the fiber surface, which seriously affects the positioning deposition of fibers and makes it difficult to obtain regular patterned fibers, greatly limiting the application areas and application effects of patterned fibers. Therefore, the improvement and innovation of the spinning process is particularly urgent. Based on material-field model and contradiction matrix of TRIZ theory, the problems of melt electrospinning device are systematically analyzed. The technical conflicts are solved by the inventive principles. A three-dimensional mobile magnetic melt spinning device model is constructed, a magnetic spinning test prototype is developed, and the prototype performance and influencing factors are studied by fiber morphology. The results show the following: (1) Replacing electrostatic fields with permanent magnetic fields can fundamentally avoid safety hazards such as electric field breakdown. (2) The magnetic field force on the molten polymer fluid can generate enough stretching force to overcome the surface tension and form fibers. (3) The fibers are deposited without a whipping instability phase similar to the electrospinning process, allowing easy preparation of regular patterned fibers. (4) The planar motion of the collector creates additional stretching effect on the fibers, which can further reduce the fiber diameter. (5) In magnetic spinning, no external high-voltage power supply is required, enabling the portability of the device. The results of this paper can provide a new method for preparing nanofibers with patterned morphology.